MYCN: from oncoprotein to tumor-associated antigen - Pistoia, Vito; Morandi, Fabio; Pezzolo, Annalisa; Raffaghello, Lizzia; Prigione, Ignazia (Frontiers in Oncology, 2012)
MYCN is a well known oncogene overexpressed in different human malignancies including neuroblastoma, rhabdomyosarcoma, medulloblastoma, astrocytoma, Wilms’ tumor and small cell lung cancer. In the case of neuroblastoma (NB), MYCN amplification is an established biomarker of poor prognosis. MYCN belongs to a family of transcription factors (the most important of which is CMYC) that show a high degree of homology. Downregulation of MYC protein expression leads to tumor regression in animal models, indicating that MYC proteins represent interesting therapeutic targets. Pre-requisites for a candidate tumor-associated antigen (TAA) to be targeted by immunotherapeutic approaches are the following, i) expression should be tumor-restricted, ii) the putative TAA should be up-regulated in cancer cells and iii) protein should be processed into immunogenic peptides capable of associating to MHC molecules with high affinity. Indeed, the MYCN protein is not expressed in human adult tissues and upregulated variably in NB cells, and MYCN peptides capable of associating to HLA-A1 or –A2 molecules with high affinity have been identified. Thus the MYCN protein qualifies as putative TAA in NB. Additional issues that determine the feasibility of targeting a putative TAA with cytotoxic T lymphocytes (CTL) and will be here discussed are the following, i) the inadequacy of tumor cells per se to act as antigen-presenting cells witnessed, in the case of NB cells, by the low to absent expression of HLA- class I molecules, the lack of costimulatory molecules and multiple defects in the HLA class I related antigen processing machinery, and ii) the immune evasion mechanisms operated by cancer cells to fool the host immune system, such as up-regulation of soluble immunosuppressive molecules (e.g. soluble MICA and HLA-G in the case of NB) or generation of immunosuppressive cells in the tumor microenvironment. A final issue that deserves consideration is the strategy used to generate CTL